Transforming Investment Banking Middle Office: A Framework for Advanced Security and Data Management - Swamy Biru (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Investment banking middle offices face unprecedented challenges in managing data consistency across their complex ecosystems. This article presents an innovative framework leveraging artificial intelligence to address critical data management issues in trade processing, risk assessment, and regulatory compliance. By examining the current landscape of siloed systems and manual reconciliation processes, this article introduces a comprehensive solution architecture that combines deep learning models, natural language processing, and advanced ETL pipelines. The proposed framework demonstrates significant improvements in data harmonization, real-time processing, and automated reconciliation while ensuring regulatory compliance. This article introduces a scalable, microservices-based architecture that effectively bridges the gap between front and back office operations, substantially reducing manual intervention and error rates. This article provides technical leaders and architects with practical insights into implementing AI-driven solutions for middle office transformation, addressing both immediate operational challenges and long-term scalability requirements. This article suggests that intelligent automation and predictive reconciliation can fundamentally transform middle office operations, leading to enhanced operational efficiency and reduced regulatory risk.